Organizational patterns in the administration guidance services - Hatch, Raymond N. (Education quarterly.)
The three topics reviewed here maybe identified as: the meaning of the term, educational leadership; the lack of functional organization in the administration of the school; and, lack of staff understanding of the various functions and roles to be played.